System dynamics in project management : assessing the impacts of quality failure on project performance - Fatin Athirah Ibrahim, 1988-, author 610967; Syed Ahmad Helmi Syed Hassan, supervisor 617573; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri))